THE COMMUNITY’S KNOWLEDGE LEVEL OF THE USE OF TRADITIONAL MEDICINES AS AN ALTERNATIVE MEDICINE IN DESA IMBANAGARA KABUPATEN CIAMIS - Fuzi Khoirurifa; Ilham Alifiar; Vera Nurviana (Borneo Journal of Pharmascientech, 2020)
Traditional medicine is an ingredient or a compound which comes from animals, plants, herbal preparations (galenic), and minerals that have been used from generation to generation for treatment and can be applied in the community according to the existing norms in their society. Indonesia has unlimited natural resources and biodiversity, also known as an agricultural country, 40% of Indonesian people use traditional medicine and 70% of them come from rural areas. This study aims to discover the level of public knowledge regarding the use of traditional medicine. Methodology used in this research was observational with a cross sectional research design and the sampling technique used was nonrandom sampling with a purposive sampling approach. The number of samples obtained in this study were 103 respondents who met the inclusion and the exclusion criteria. The results showed that the level of knowledge of the people in Desa Imbanagara regarding traditional medicine was sufficient (48.5%). The reason of why people in Desa Imbanagara use traditional medicines is because it is easy to get (32%), the purpose of using traditional medicine is to cure sudden or minor illnesses (68.9%), the place or the way to get traditional medicine is in a small shop (54.4%), the average use of traditional medicine is 2 - 3 days (37.9%), sources of information obtained from family and / or friends (51.5%). In conclusion, the level of knowledge of the people in Desa Imbanagara regarding traditional medicine is sufficient.